Carotenoid producing Bacillus aquimaris found in chicken gastrointestinal tracts - Luong, Tran Thi; Huong, Ngo Thi; Ha, Bui Thi Viet; Huong, Pham Thi Thu; Anh, Nguyen Hoa; Huong, Do Thi Viet; Van, Quach Thi Ha; Nghia, Phan Tuan; Anh, Nguyen Thi Van (Vietnam Journal of Biotechnology, 2018)
Pigmented spore-forming bacterial strains were isolated from the gastrointestinal tracts of chickens for screening for heat-stable carotenoid-producing strains that could be applied as feed supplements. Of the seven heat-stable pigmented isolates screened, only two, yellow Sporosarcina saromensis CH1 and red-orange Bacillus aquimaris CH9, produced pigments with typical carotenoid absorbance peaks (400–500 nm). The CH9 carotenoids exhibited higher scavenging activity (73.2%) of DPPH free radicals than the CH1 carotenoids (35.9%) and carotenoids of the reference B. indicus HU36 strain (78.4%), in comparison to 100% activity of acid ascorbic at 18.75 M as the standard. The CH9 strain produced high levels of carotenoids (439 g [g DW]-1) and formed nearly 100% spores, whereas the CH1 strain produced low levels of carotenoids (92 g [g DW]-1) and only achieved 30% sporulation. Chromatographic and spectral profiles of the carotenoids found in CH9 indicated the presence of as many as 11 different carotenoid types closely related to 1-HO-demethylspheroidene and keto/hydroxyl derivatives of  carotene. We successfully produced concentrated orange CH9 spore powder at a high concentration of 6.1 × 1011 CFU g-1; these spores were much more heat-stable (66% survival at 80°C for 20 min) than the reference B. indicus HU36 spores (9% survival at 50°C for 20 min). In conclusion, B. aquimaris CH9 is a promising probiotic carotenoid-producing strain, with heat-stable spores that should withstand the heat-treatment processing required for feed and food supplement production